Júlia Lopes de Almeida e sua trajetória de consagração em o país - Tamba, Nahete de Alcântara da silva (2015)
The newspaper had the late nineteenth century and early twentieth century as the period when it was confirmed as the main written circulation support and dissemination of literary work in Brazil. It became an important gateway for those who wanted to enter the world of Literature. Following this trend, Júlia Lopes de Almeida made her career and her literary work by means of the press. In order to achieve the main aim in this thesis, we traced a path that could reveal to us the development of her literary stamp production. And so we registered the publications that led to the consecration of that writer. Therefore, starting from the collection of the periodic productions, we chose the newspaper O País that, in turn, was the main diffusion vehicle of the writings of Julia Lopes through which stood out each of the genres that make up the body of her literary work in the daily publication. Following after drawing the newspaper profile in question, we gave emphasis to the registration of which was published by the author emphasizing its production series and unpublished writings. The appendices constitute the written record referred to in the thesis.